Unveiling Complexity: Cinematic Representations of Apartheid History and the Post-Apartheid Dutch- Afrikaner Relationship in Black Butterflies (2011) and An Act of Defiance (2017) - Anne Marieke van der Wal (Tijdschrift voor Mediageschiedenis, 2024)
The cinematic representation of Apartheid, and in particular the tendency of using white protagonists to narrate the story of black suffering, has been the object of much scholarly enquiry but this has never included Dutch films. This article explores the representation of Afrikaner anti-Apartheid activism in Dutch cinema through an analysis of the films Black Butterflies (2011) and An Act of Defiance (2017). It investigates how these films perpetuate or challenge the paradigm of ‘white heroism’ and ‘white saviourism’ prevalent in cinematic portrayals of colonial and Apartheid history. Through a comparative study, it reveals nuanced narratives of white protagonists, highlighting their complexities as ‘tragic heroes’ rather than conventional ‘white saviours,’ yet at the same time suggesting a societal inclination towards absolving their past sins, echoing a broader post-Apartheid narrative of forgiveness and reconciliation. By contextualising these representations within broader societal discourses on colonialism and post-Apartheid reconciliation, the article sheds light on evolving Dutch attitudes towards Afrikaners, as the descendants of Dutch colonists, and their historical culpability, offering insights into contemporary Dutch engagement with issues of race, identity, and historical memory.